A permeabilidade inquisitória do processo penal em relação aos atos de investigação preliminar - Souza, David Tarciso Queiroz de (2016)
This dissertation is on the reflexes brought to the penal process and the final judicial decision by the introduction of acts of investigation, through police inquiry. The author chose to analyse preliminary investigation emphasizing its authoritarian and inquisitive aspects, remarking the values attributed to the acts of investigation thoughout the penal process, aiming to show how deleterious it is to the impartiality of the judge and, consequently, to the healthy application of law the contamination of the process by the acts of investigation.